Attenuated accumulation of regulatory T cells and reduced production of interleukin 10 lead to the exacerbation of tissue injury in a mouse model of acute respiratory distress syndrome. (15th February 2018) - Toyama, Masahiko; Kudo, Daisuke; Aoyagi, Tetsuji; Miyasaka, Tomomitsu; Ishii, Keiko; Kanno, Emi; Kaku, Mitsuo; Kushimoto, Shigeki; Kawakami, Kazuyoshi
ABSTRACT: Acute respiratory distress syndrome (ARDS) is a pathological condition that involves diffuse lung injury and severe hypoxemia caused by pulmonary and systemic diseases. We have established a mouse model of severe ARDS, developed by intratracheal injection of α‐galactosylceramide (α‐GalCer), an activator of natural killer T (NKT) cells, followed by LPS. In the present study, we used this model to investigate the regulatory mechanism in the early inflammatory response during acute lung injury. In α‐GalCer/LPS‐treated mice, the number of CD4 + CD25 + Foxp3 + regulatory T (Treg) cells and the expression of a Treg cell‐tropic chemokine, secondary lymphoid‐tissue chemokine (SLC), in the lungs was significantly lower than in mice treated with LPS alone. Giving recombinant (r)SLC increased the number of Treg cells in α‐GalCer/LPS‐treated mice. Treatment with anti‐IFN‐γ mAb enhanced the expression of SLC and the accumulation of Treg cells in the lungs of α‐GalCer/LPS‐treated mice, whereas giving recombinant (r)IFN‐γ reduced the number of Treg cells in mice treated with LPS alone. IL‐10 production was significantly lower in α‐GalCer/LPS‐treated mice than in mice treated with LPS alone. Giving rIL‐10 prolonged survival and attenuated lung injury as a result of reduced production of inflammatory cytokines (such as IL‐1β, IL‐6, TNF‐α, and IFN‐γ) and chemokines (including MCP‐1, RANTES, IP‐10, Mig, MIP‐2, and KC) in α‐GalCer/LPS‐treated mice. Treatment with anti‐IFN‐γ mAb enhanced IL‐10 production in α‐GalCer/LPS‐treated mice. These results suggest that the attenuated accumulation of Treg cells may be involved in the development of severe ARDS through a reduction in the synthesis of IL‐10.